Study of the Physiochemical and Nutraceutical Properties of Sour and Sweet Pomegranate Juice in Northern Jordan - Taha Rababah; Muhammad Al-U’datt; Sana Gammoh; Tayma’a Khatatbeh; Ghazi Magableh; Ali Almajwal; Sevil Yücel; Numan AL-Rayyan (Journal of Food Quality)
Pomegranate juice (PJ) is the major pomegranate product that offers a simple way to consume pomegranate’s biologically active compounds, obtained from arils. In this study, we objectively investigate the physiochemical properties such as pH value, total soluble solids, color parameters, fructose and glucose contents, hydroxymethyl furfural (HMF) content, and viscosity. Also, the phytochemical content includes total phenols content, antioxidant activity, flavonoid, anthocyanin content, and phenolic quantification. In addition, the alpha-amylase and angiotensin-converting enzyme inhibitory activities among sweet and sour varieties of pomegranate juice obtained from different regions in Northern Jordan (Ajloun, Dair Abi Said, and Kufur Soum) where the significant differences at P ≤ 0.05 appeared among sweet and sour varieties in different pomegranate juice samples. The pH values for pomegranate juice range from 2.87 to 3.77, and TSS ranges from 15.36 to 16.9 Brix. The total phenol content of pomegranate juice ranged from 105.8 to 238.63 mg/g while the total flavonoid content was present in the range of 135.53–184.9 mg/g. The DPPH inhibition (%) of pomegranate juice ranged between 20.66% and 50.63%, and the anthocyanin content range was 3.66–11.02 mg/g. Ellagic acid, delphinidin, 3,4-dihydroxyphenethyl alcohol, 2-hydroxyphenethyl alcohol, catechin, epicatechin, vanillic acid, caffeic acid, P-coumaric acid, chlorogenic acid, gallic acid, ferulic acid, and syringic acid are phenolics present predominantly in pomegranate juice. Pomegranate juice exhibits high alpha-amylase and angiotensin-converting enzyme inhibition activity. All results indicate good quality and health properties for pomegranate juice.